1995
DOI: 10.1111/j.1365-2591.1995.tb00317.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of the indirect action of calcium hydroxide on the anaerobic flora of the root canal

Abstract: The aim of this study was to evaluate in vitro a possible mechanism involved in the antimicrobial action of calcium hydroxide, namely absorption of carbon dioxide from the root canal. Twenty obligate and 20 facultative anaerobic bacteria isolated from infected root canals and identified to species level were used. For each bacterial species a standard concentration was achieved and 0.1 ml of the inoculum was spread on blood agar plates, which were consecutively incubated in an anaerobic chamber for 5-7 days. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 27 publications
1
37
0
7
Order By: Relevance
“…At low concentrations, chlorhexidine has bacteriostatic effect due to the leakage out of small molecular weight substances. At higher concentrations, CHX precipitate and/or coagulate the cytoplasm which results in bactericidal effect [35]. In this study, 2% CHX showed high antibacterial activity in disk diffusion test with 30 mm zone of inhibition, but it was excluded from MIC experiment due to instant precipitation and turbidity that occurred after CHX and Mueller Hinton were mixed [36].…”
Section: Discussionmentioning
confidence: 99%
“…At low concentrations, chlorhexidine has bacteriostatic effect due to the leakage out of small molecular weight substances. At higher concentrations, CHX precipitate and/or coagulate the cytoplasm which results in bactericidal effect [35]. In this study, 2% CHX showed high antibacterial activity in disk diffusion test with 30 mm zone of inhibition, but it was excluded from MIC experiment due to instant precipitation and turbidity that occurred after CHX and Mueller Hinton were mixed [36].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, its use as an intracanal medication has increased 9,16,[19][20][21] . In addition, calcium hydrox ide is suggested to be useful for destroying anaerobic bacteria, which are frequently detected in highlyinfected root canals 13) . Taken together, the use of formaldehyde preparations as intracanal medications has decreased, while the use of calcium hydrox ide for the same purpose has increased in Europe and the US.…”
Section: Intracanal Medicamentmentioning
confidence: 99%
“…수산화 칼슘은 세균의 lipopolysaccharide를 분해하고 7,8) , 세균의 기질이 될 수 있는 괴사 조직의 잔사를 용해시킬 수 있기 때 문에 살균 효과를 나타낸다 9,10) . 또한, 수산화칼슘으로 근관 을 밀폐시키면 조직 삼출액의 유입을 효과적으로 차단하여 세균의 영양분이 공급되는 것을 감소시키며 11) , 세균의 생존 에 필요한 근관내의 이산화탄소를 흡수하기 때문에 부가적 인 살균 효과를 나타낸다 12) . 그리고, 치근단 조직내로 수산 화칼슘이 정출되면서 대식세포의 물질부착 능력을 감소시 켜 염증반응을 감소시킬 수 있다 13) .…”
unclassified